PERSEPSI MAHASISWA TERHADAP PROFESI GURU - Luthfi Ardiansyah; Santoso Sri Handoyo; Amos Neolaka (Jurnal Pensil : Pendidikan Teknik Sipil, 2012)
This research aims to determine the student’s perception to the professional teacher in Building Construction Education Study Program State University of Jakarta students. The research is conducted in epartment of Civil Engineering State University of Jakarta in January 2012. The method used in this research is surveying method with likert scale 1 to 4 (1-4). The population of this research is 141 students of Building Construction Education Study Program State University of Jakarta school year 2007 and 2008. Numbers of samples are 56 students which are determined using Yamane calculation and simple random sampling method. The instrument used is using questionnaire to collect the student’s perception to the professional teacher. From the calculation, we get the reliability value is very high r11 = 0.935 where the total number of questions are 38 problems. Wholly the student’s perception to the professional teacher based on teacher’s needed indicator is good with the average score is 3.03, based on pedagogic competence indicator is also good with the average score 3.33, and based on professional competence indicator is good with the average score 3.16. The conclusion of indicator to the student’s perception is good, but the sub indicator of profession reward has the average score 2.75. So we can see that the student prefer to choose the non educational program (professional program) to educational program. Further the student’s perception to the pedagogic and professional aspect is good, it means that the students understand about the duty and responsibility of the professional teacher. Based on those conclusions, we would like to suggest that the students keep on improving their knowledge about the pedagogic competence and professional competence to be competent teachers so that they are able to conduct the learning process